ADULT-ONSET FOVEOMACULAR VITELLIFORM DYSTROPHY EVALUATED BY MEANS OF OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY: A Comparison With Dry Age-Related Macular Degeneration and Healthy Eyes. Issue 4 (April 2018) - Toto, Lisa; Borrelli, Enrico; Mastropasqua, Rodolfo; Di Antonio, Luca; Mattei, Peter A.; Carpineto, Paolo; Mastropasqua, Leonardo
Abstract : Purpose: To investigate alterations of superficial and deep retinal vascular densities, as well as of choroidal thickness, in patients affected by adult-onset foveomacular vitelliform dystrophy (AOFVD). Methods: A total of 22 eyes (15 patients) affected by AOFVD were recruited in the study. Furthermore, 20 eyes of 20 healthy subjects and 20 eyes of 18 patients affected by intermediate dry age-related macular degeneration (AMD) were enrolled. All patients underwent a complete ophthalmologic examination, including optical coherence tomography angiography. Outcome measures were superficial vessel density, deep vessel density, and choroidal thickness. Results: Parafoveal superficial vessel density was increased in patients with AOFVD compared with the AMD group (50.6 ± 4.3% and 46.3 ± 4.3%, respectively, P = 0.016). Parafoveal deep vessel density was 57.9 ± 6.4% in patients with AOFVD, 52.2 ± 3.8% in patients with AMD, and 52.7 ± 6.0% in healthy controls ( P = 0.006 and P = 0.035, respectively, after comparison with the AOFVD group). Conclusion: We demonstrated that both superficial and deep vessel densities were significantly increased in patients with AOFVD, after the comparison with intermediate patients with AMD. These findings suggest that the pathogenic mechanisms in AOFVD are different from those in AMD and that optical coherence tomography angiography could be useful in differentiate early stages of these two diseases. Abstract : In eyes affected by adult-onset foveomacular vitelliform dystrophy, the optical coherence tomography angiography shows changes in vessel density, after the comparison with both age-related macular degeneration and healthy eyes.